STUDIES ON THERMAL DEFFUSIVITY AND CONDUCTIVITY OF FRESHWATER AND DRY FISH - ANNAMMA, T T; RAO, C V.N (Fishery Technology, 2017)
Thermal diffusivity (cr) and conductivity (K) of fresh and dry'cured fish at different moisture levels were investigated byacalorimeter (regular regime) method and transient line sourcetechnique. Thermal conductivity has a linear correlationwith packing density and percentage water content.K values calculated from formula method and line sourcetechnique are comparable